Чисельний аналіз структурним методом R-функцій електростатичних полів в плоских областях з геометричними сингулярностями - Галін, П. К. (ХНУРЕ, 2023)
This paper considers the application of the structural method of R-functions to the solution of the problem of mathematical modeling of electrostatic fields in planar regions with geometrical singularities. Classical solution structures in this case lose the property of completeness. We describe an approach to transform such a structure into an exact one and obtain numerical results for calculating the electrostatic field in a region with an insulator.
Keywords: чисельний аналіз; структурний метод R-функцій; електростатичне поле; плоска область; геометрична сингулярність